A case of peripheral ameloblastoma that developed in the maxillary gingiva of child. Issue 4 (July 2020) - Yamanaka, Shigeki; Nakao, Kazumasa; Nishikawa, Yuya; Kashiwagi, Marina; Mishima, Sayaka; Kataoka, Tatsuki; Sonobe, Junya; Bessho, Kazuhisa
Abstract: Peripheral ameloblastoma (PA) is an uncommon variant of ameloblastoma that occurs in extraosseous soft tissue. Our patient, a 10-year-old girl, was hospitalized with a mass in the anterior plate gingiva. The elastic hard mass was approximately 7 mm in length, the surface mucosa was normal, and no spontaneous or oppressive pain was present. Computed tomographic and panoramic X-ray examination revealed no infiltration into the anterior plate. First, we performed biopsy of the mass; pathologic study revealed that the tumor was a PA. The prognosis of patients with PA is generally good, but recurrence has been reported. In surgery, we resected the tumor with 5-mm margins, which included the periosteum. After surgery, no recurrence was observed, and the wound healed well. No evidence of recurrence was found at follow-up observation, but we plan to continue monitoring the patient carefully.